Relationality With the Dead in Chinese Sufism: Relics’ Agency and Self-Annihilation in the Afterlives of Two Jahriyya Shaykhs - Previato, Tommaso (Omega-Journal of Death and Dying, 2025)
This paper interrogates what place do dead exemplars and saintly relics occupy in the ritual repertoire of Jahriyya Sufism – a mystical revivalist movement that emerged in mid-18th century Northwest China as a sectarian offshoot of the Yemeni Naqshbandi tradition. Since its inception, the Jahriyya played a leading role in the Muslim uprisings against the Qing dynasty (1644–1912). The paper proposes a model of relationality with the dead where mortuary practices are not aimed solely at memorializing the shaykhs who fell as martyrs in the uprisings, but, most importantly, at aiding Sufi initiates in their inner-directed effort to transcend egoistic desires and eventually uncover God’s qualities within themselves – a practice that in classical Sufism is called fanā’ fir-Allah (lit. “self-annihilation in God”).
CRIS-Team Scopus Importer:2025-01-31
Keywords: fanā’ fir-Allah; Jahriyya; mortuary practices; relationality; relics’ agency